2020
DOI: 10.1111/ced.14309
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibition of regulatory CD4+CD25+T cells in peripheral blood of patients with pemphigus vulgaris

et al.

Abstract: Summary Background Pemphigus vulgaris (PV) is a potentially life‐threatening autoimmune bullous disease affecting the skin and mucous membranes. Its pathogenic mechanism is still not fully understood. Regulatory T cells (Tregs) have been reported to play a significant role in regulating immune homeostasis in autoimmune disorders, such as PV. Aim To investigate the potential role of Tregs in the immunopathogenesis of PV. Methods We enrolled 15 patients with PV and 15 healthy controls (HCs). Peripheral blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
2
1
0
1
Order By: Relevance
“…These findings are consistent with a recent study that found functional suppression of regulatory CD4 + CD25 + T cells in the peripheral blood of PV patients 19 . This suggests a problem with Tregs, either in terms of number or function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with a recent study that found functional suppression of regulatory CD4 + CD25 + T cells in the peripheral blood of PV patients 19 . This suggests a problem with Tregs, either in terms of number or function.…”
Section: Discussionsupporting
confidence: 93%
“…mean values and percentage of skin lesional Tregs (CD 25 +, % CD 25 / CD4, Foxp 3 +, and % Foxp 3 / CD 4 ) in pemphigus patients compared with healthy controls and this result was in agreement with Xu et al, who found that Treg cells in pemphigus patients' blood measured by fluorescence-activated cell sorting were significantly fewer than in the control group, and also according to Sugiyama et al, the fraction of CD4+CD25+ Tregs among total CD4+ T cells in the blood ofPV patients was significantly lower than in controls, almost 10-fold lower 17,18. These findings are consistent with a recent study that found functional suppression of regulatory CD4 + CD25 + T cells in the peripheral blood of PV patients 19. This suggests a problem with Tregs, either in terms of number or function Terras et al (2014) 20 ,.…”
supporting
confidence: 89%
“…Conversely, in MG mediated by predominantly IgG1 autoantibodies against AChR, patients have been shown to harbor dysfunctional Tregs (95), and further, induction of Tregs via GM-CSF effectively suppressed experimental autoimmune MG (96). In pemphigus vulgaris (PV) mediated by predominantly IgG4 autoantibodies against desmoglein, contradicting data that Tregs have both not been able to suppress (97) and have suppressed autoimmune responses (98) are reported. These results underline the need for further investigations into the role of Tregs in autoantibodymediated autoimmunity.…”
Section: Mechanistic Differences Between Igg1 and Igg4 Responsesmentioning
confidence: 99%
“…Por otro lado, Su et al 40 no encontraron diferencia en los niveles de nTreg periféricas entre sujetos con PV y controles sanos, aunque observaron que la capacidad supresora de estas células estaba disminuida.…”
Section: Funcionesunclassified